Human Finger‐Prick Induced Pluripotent Stem Cells Facilitate the Development of Stem Cell Banking. (19th March 2014) - Tan, Hong-Kee; Toh, Cheng-Xu Delon; Ma, Dongrui; Yang, Binxia; Liu, Tong Ming; Lu, Jun; Wong, Chee-Wai; Tan, Tze-Kai; Li, Hu; Syn, Christopher; Tan, Eng-Lee; Lim, Bing; et al.
Abstract : Human induced pluripotent stem cells (hiPSCs) can be easily and efficiently generated from finger‐prick blood. Using this collection method will accelerate the development of large‐scale hiPSC banks. Abstract : Induced pluripotent stem cells (iPSCs) derived from somatic cells of patients can be a good model for studying human diseases and for future therapeutic regenerative medicine. Current initiatives to establish human iPSC (hiPSC) banking face challenges in recruiting large numbers of donors with diverse diseased, genetic, and phenotypic representations. In this study, we describe the efficient derivation of transgene‐free hiPSCs from human finger‐prick blood. Finger‐prick sample collection can be performed on a "do‐it‐yourself" basis by donors and sent to the hiPSC facility for reprogramming. We show that single‐drop volumes of finger‐prick samples are sufficient for performing cellular reprogramming, DNA sequencing, and blood serotyping in parallel. Our novel strategy has the potential to facilitate the development of large‐scale hiPSC banking worldwide.